Community health workers at the dawn of a new era: 3. Programme governance - Simon Lewin; Uta Lehmann; Henry B. Perry (BMC, 2021)
Abstract Background Community health workers (CHWs) can play a critical role in primary healthcare and are seen widely as important to achieving the health-related Sustainable Development Goals (SDGs). The COVID-19 pandemic has emphasized the key role of CHWs. Improving how CHW programmes are governed is increasingly recognized as important for achieving universal access to healthcare and other health-related goals. This paper, the third in a series on "Community Health Workers at the Dawn of a New Era", aims to raise critical questions that decision-makers need to consider for governing CHW programmes, illustrate the options for governance using examples of national CHW programmes, and set out a research agenda for understanding how CHW programmes are governed and how this can be improved. Methods We draw from a review of the literature as well as from the knowledge and experience of those involved in the planning and management of CHW programmes. Results Governing comprises the processes and structures through which individuals, groups, programmes, and organizations exercise rights, resolve differences, and express interests. Because CHW programmes are located between the formal health system and communities, and because they involve a wide range of stakeholders, their governance is complex. In addition, these programmes frequently fall outside of the governance structures of the formal health system or are poorly integrated with it, making governing these programmes more challenging. We discuss the following important questions that decision-makers need to consider in relation to governing CHW programmes: (1) How and where within political structures are policies made for CHW programmes? (2) Who implements decisions regarding CHW programmes and at what levels of government? (3) What laws and regulations are needed to support the programme? (4) How should the programme be adapted across different settings or groups within the country or region? Conclusion The most appropriate and acceptable models for governing CHW programmes depend on communities, on local health systems, and on the political system in which the programme is located. Stakeholders in each setting need to consider what systems are currently in place and how they might be adapted to local needs and systems.